Deciphering the role of evapotranspiration in declining relative humidity trends over land - Yeonuk Kim; Mark S. Johnson (Communications Earth & Environment)
Abstract In recent decades, relative humidity over land has declined, driving increases in droughts and wildfires. Previous explanations attribute this trend to insufficient moisture advection from the ocean to sustain the current level, but this ignores atmospheric moisture supplied from terrestrial evapotranspiration. Importantly, current state-of-the-art climate models continue to underestimate the observed relative humidity trend over land. Here, we show that changes in specific humidity over land relative to a given baseline, unaccounted for by ocean advection, are quantitatively equivalent to relative changes in evapotranspiration on a global scale. This finding is consistent across climate models and climate reanalysis datasets, despite discrepancies in evapotranspiration trends among them. Differences in evapotranspiration trends are identified as a prominent cause of the bias in relative humidity trend expressed in climate models. These results suggest that current climate models may overestimate evapotranspiration intensifications, leading to an underestimation of atmospheric drying, with critical implications for accurately predicting droughts, wildfires, and climate adaptation.